Investigation of Light Parameters on Image Quality and Optical Coherence Tomography - Boka Fikadu; Bulcha Bekele; Leta Tesfaye Jule; Anatol Degefa; N. Nagaprasad; Krishnaraj Ramaswamy (International Journal of Optics)
In this work, image quality and optical coherence tomography were studied. The results of the study show that there is a very significant difference between ultrasound and optical coherence tomography to produce an image with a different wave. To understand this, we studied the basic principle of optical coherence tomography in the Michelson interferometer using monochromatic and broadband sources. Time-domain and spectral-domain measurements, which exist at the detector level, are briefly described using a glass sample. The time-domain signal strength of the Michelson interferometer using a broadband source is a Gaussian envelope.